Experience Summary of Laparoscopic Treatment for Pediatric Ureteral Polyps - Gao, Hongjie; Chen, Jiawei; Li, Guowei; Cui, Xinhai; Sun, Fengyin (Frontiers in Pediatrics, 2021)
To investigate surgical techniques and challenges of laparoscopic in treating pediatric ureteral polyps under laparoscopy. Methods: The clinical data of 7 of pediatric ureteral polyps patients who were admitted to the hospital from July 2015 to January 2020 were analyzed retrospectively. There were 6 males and 1 female from 7.7 to 13.9 years old at the mean age of 10.4. Before surgery, all children performed urinary B ultrasound, magnetic resonance urography (MRU), and renal radionuclide scanning. Six cases were observed on the left lateral and 1 on the right. The lesions of 5 cases were located at the ureteropelvic junction, 1 in the upper ureter and 1 in the middle ureter. The polyps were treated intraoperatively by the resecting of the lesion segment and simple polypectomy to retain the attached part of the original diseased segment of the ureter. All surgeries were performed under laparoscopy and B-ultrasound was performed during follow up after surgery. Results: All 7 surgeries were performed successfully under the laparoscope. The surgery time was 80-110 min, and the average surgery time was 97.5 min. The intraoperative bleeding was 10-25 ml and the average postoperative hospital stay was 6d. Postoperative hematuria occurred in 1 case. Neither urinary leakage nor urinary tract infection was reported post surgery. Preoperative affected pyelectasis of all patients was 2.0-3.7 cm. Three months postoperatively, the affected pyelectasis was measured at 1.2-3.0 cm. No recurrence of polyps was reported after surgery. During the follow-up to April 2020, there was no significant change in the kidney size of all patients, and hydronephrosis was alleviated compared with that before surgery. Conclusions: Laparoscopy is a safe, effective and minimally invasive surgical technique for pediatric multiple ureteral polyps. The surgery plan was designed according to the location and size of polyps, including segmental ureterectomy of polyps + pyeloureterostomy, segmental ureterectomy of polyps + ureter - ureteral anastomosis.